Prognostic Role of Neutrophil-to-Lymphocyte Ratio in Solid Tumors: A Systematic Review and Meta-Analysis. (29th May 2014) - Templeton, Arnoud J.; McNamara, Mairéad G.; Šeruga, Boštjan; Vera-Badillo, Francisco E.; Aneja, Priya; Ocaña, Alberto; Leibowitz-Amit, Raya; Sonpavde, Guru; Knox, Jennifer J.; Tran, Ben; Tannock, Ian F.; Amir, Eitan
Abstract: Background: Inflammation may play an important role in cancer progression, and a high neutrophil-to-lymphocyte ratio (NLR) has been reported to be a poor prognostic indicator in several malignancies. Here we quantify the prognostic impact of this biomarker and assess its consistency in solid tumors. Methods: A systematic review of electronic databases was conducted to identify publications exploring the association of blood NLR and clinical outcome in solid tumors. Overall survival (OS) was the primary outcome, and cancer-specific survival (CSS), progression-free survival (PFS), and disease-free survival (DFS) were secondary outcomes. Data from studies reporting a hazard ratio and 95% confidence interval (CI) or a P value were pooled in a meta-analysis. Pooled hazard ratios were computed and weighted using generic inverse-variance and random-effect modeling. All statistical tests were two-sided. Results: One hundred studies comprising 40559 patients were included in the analysis, 57 of them published in 2012 or later. Median cutoff for NLR was 4. Overall, NLR greater than the cutoff was associated with a hazard ratio for OS of 1.81 (95% CI = 1.67 to 1.97; P < .001), an effect observed in all disease subgroups, sites, and stages. Hazard ratios for NLR greater than the cutoff for CSS, PFS, and DFS were 1.61, 1.63, and 2.27, respectively (all P < .001). Conclusions: A high NLR is associated with an adverse OS in many solid tumors. The NLR is a readily available and inexpensive biomarker, and its addition to established prognostic scores for clinical decision making warrants further investigation.